Spiritual Leadership in Healthcare: A Bibliometric Analysis - Dienda Sesioria Assyakur; Elsye Maria Rosa (Universitas Aisyah Pringsewu, 2022)
Spiritual leadership is one of the leadership styles that are currently popular in management studies. It has vision, hope, faith, and altruistic love to create a positive environment in an organization. Goals. Provide information through bibliometric analysis of publishing patterns, literature developments, and information analysis of spiritual leadership research publications. This study included quantitative descriptive approaches and bibliometric analyses to map bibliographic data from various journal articles from the Scopus database using VOSviewer. This study retrieves data on December 15, 2021, using the keywords